2018
DOI: 10.1002/jcb.28029
|View full text |Cite
|
Sign up to set email alerts
|

The role of Bag2 in neurotoxicity induced by the anesthetic sevoflurane

Abstract: Sevoflurane is the most commonly used general anesthetic in pediatric patients. But preclinical studies indicate that sevoflurane could have neurotoxicity in newborn and old animals, and this raises concern regarding its safety. In this study, we explored the potential mechanisms of sevoflurane‐induced neurotoxicity in human SH‐SY5Y neuronal cells. We showed that prolonged exposure to 2% sevoflurane caused a significant increase in the Bag family protein Bag2 in a time‐ and dose‐dependent manner. We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Numerous evidences have shown that BAG2 plays a substantial role in the pathogenesis of neurodegenerative diseases and neurotoxicity, such as Alzheimer's disease (14), Parkinson's disease (15), sevoflurane-induced neurotoxicity (16), etc. In recent years, the role of BAG2 in cancer has significantly attracted scholars' attention.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous evidences have shown that BAG2 plays a substantial role in the pathogenesis of neurodegenerative diseases and neurotoxicity, such as Alzheimer's disease (14), Parkinson's disease (15), sevoflurane-induced neurotoxicity (16), etc. In recent years, the role of BAG2 in cancer has significantly attracted scholars' attention.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical study has shown that children exposed to sevoflurane demonstrated higher apoptosis status of neural stem cells [16]. Moreover, anesthetic sevoflurane could also induce neurotoxicity in neuronal cells with decreased cell viability and increased cell apoptosis [17]. The data from this study showed that exposure of the isolated neurons from neonatal rats to sevoflurane induced severely neurotoxicity with decreased cell viability and increased cell apoptosis.…”
Section: Discussionmentioning
confidence: 56%
“…Antioxidant defense was increased in children exposed to sevoflurane [16], and levels of reactive oxygen species were also accumulated in neonatal rats post sevoflurane exposure [4]. The reduction of reactive oxygen species was shown to be helpful for the amelioration of sevoflurane-induced neurotoxicity [17]. TRPM7 could release Zn 2+ through sensation of oxidative stress [18].…”
Section: Discussionmentioning
confidence: 99%
“…As a commonly used anesthetic for general anesthesia, sevoflurane has been shown to be potentially neurotoxic to the developing brain (Qi et al, 2018; Yang et al, 2017). Ngb, an endogenous protein, has a neuroprotective effect on a variety of central nervous system diseases, such as stroke (Ren et al, 2015; Yu et al, 2018), ischemic and hypoxic brain injury (Wen et al, 2018) and neurodegenerative diseases (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%